Trends in Brazilian market of antidepressants: A five-year dataset analysis - Rogério Hoefler; Rogério Hoefler; Taís Freire Galvão; Inês Ribeiro-Vaz; Inês Ribeiro-Vaz; Marcus Tolentino Silva (Frontiers Media S.A., 2022)
Introduction: Depression is an emotional disorder associated with morbidities and disabilities worldwide. The growing use of antidepressants is a concern for health managers because there are still unanswered questions on the effectiveness and safety of these medicines. Drug sales have increased in Brazil in recent years, but investigations on antidepressants sales are not available. We aimed to describe the trends in the antidepressant commerce in Brazil in a five-year period.Materials and Methods: We performed an ecological study on antidepressant sales in Brazil, from November 2014 to October 2019, using data from IQVIA™, a data provider of pharmaceutical sales. Antidepressants were coded by the Anatomical Therapeutic Chemical classification system, and sales were presented in defined daily doses (DDDs) and DDDs per 1,000 inhabitants per day (DIDs). The results were expressed in absolute quantities and growth rates.Results: The analyzed dataset contained 23 active substances in 780 products. The total sales of antidepressants increased from 23.3 DIDs in November 2014 to 38.3 DIDs in October 2019 (p = 0.002). Selective serotonin reuptake inhibitors were the most sold category of drugs (+5.7 million DDDs) in the period. 'Other' antidepressants presented the largest growth rate (104.7%). Individually, the most sold active substance was escitalopram (+1.8 million DDDs), and vortioxetine had the largest growth rate (336.2%). Tricyclic sales remained unchanged, and monoamine oxidase inhibitors had low and even decreasing sales (−9.5%).Discussion: The total sales of antidepressants increased in Brazil from November 2014 to October 2019. The higher sale volumes of selective serotonin reuptake inhibitors and higher growth rate of 'other' antidepressants, with low sale volume of tricyclics and a decrease of monoamine oxidase inhibitors, suggest the replacement of older drugs by newer ones following a global trend. Therapeutic advances and commercial promotion efforts on new products might explain these findings.